JENIS DAN POPULASI SERANGGA-SERANGGA HAMA GUDANG BIJI PALA DI KECAMATAN TUMINTING KOTA MANADO - Michael A. Lumi; Maxi Lengkong; Jantje Jantje Pelealu (Universitas Sam Ratulangi, 2021)
ABSTRACT The insects that destroy nutmeg seeds are known to be Araecerus sp., Carpophilus sp., Lasioderma sp., and Tribollium sp. Long-term storage and improper post-harvest handling will cause warehouse pests to attack which causes quality degradation and yield loss. The objectives of the study were (1) to determine the types of insect pests that attack nutmeg seeds in the warehouse and (2) to determine the population of insect pests that attack nutmeg seeds in the warehouse. This research was conducted in two ways, namely by direct capture method (hand sampling) and the use of yellow sticky trap traps. The direct capture method is carried out by taking samples of nutmeg seeds from five points, namely at the corner and center diagonally in the warehouse. The weight of the seed sample from each point was 500 grams, then put into a jar and covered with gauze. Sampling was carried out once a week five times. All samples were labeled and taken to the laboratory for calculation and species identification.Sampling using the Yellow sticky trap method is a trap made of yellow paper whose surface has been coated with adhesive glue. Yellow stick traps are hung in the nutmeg warehouse Â± 2 meters from the warehouse floor surface, which are placed around piles of nutmeg sacks. The nutmeg warehouse where the observations were made was installed with four yellow sticky traps for three days. Observations were made at intervals of three days and repeated five times. Samples of trapped insects will be taken to the laboratory for population calculations and species identification. Based on the results of the discussion, it can be concluded that the insect pests that were found attacking nutmeg seeds in the storage warehouse in Manado City with the direct capture method (hand sampling) found six species, namely Anthribidae, Laemophloeidae, Silvanidae, Ptinidae, Tenebrionidae, Nitidulidae and those obtained by trapping (yellow sticky trap) six species were found, namely Anthribidae, Silvanidae, Laemophloeidae, Tenebrionidae, Tephritidae, Hymenoptera. The highest population is Tenebrionidae with a population of 66.6 individuals obtained by direct capture method (hand sampling); and 195.5 tails obtained by trapping (yellow sticky trap) Keyword : Insect, Pest, Warehouse, Nutmeg